On‐Surface Driven Formal Michael Addition Produces m‐Polyaniline Oligomers on Pt(111). Issue 51 (12th October 2020) - Ruiz del Árbol, Nerea; Sánchez‐Sánchez, Carlos; Otero‐Irurueta, Gonzalo; Martínez, José I.; de Andrés, Pedro L.; Gómez‐Herrero, Ana C.; Merino, Pablo; Piantek, Marten; Serrate, David; Lacovig, Paolo; Lizzit, Silvano; Alemán, José; et al.
Abstract: On‐surface synthesis is emerging as a highly rational bottom‐up methodology for the synthesis of molecular structures that are unattainable or complex to obtain by wet chemistry. Here, oligomers of meta ‐polyaniline, a known ferromagnetic polymer, were synthesized from para ‐aminophenol building‐blocks via an unexpected and highly specific on‐surface formal 1, 4 Michael‐type addition at the meta position, driven by the reduction of the aminophenol molecule. We rationalize this dehydrogenation and coupling reaction mechanism with a combination of in situ scanning tunneling and non‐contact atomic force microscopies, high‐resolution synchrotron‐based X‐ray photoemission spectroscopy and first‐principles calculations. This study demonstrates the capability of surfaces to selectively modify local molecular conditions to redirect well‐established synthetic routes, such as Michael coupling, towards the rational synthesis of new covalent nanostructures. Abstract : A novel, on‐surface synthesis of oligomers of meta ‐polyaniline from para ‐aminophenol precursors by an unexpected formal 1, 4 Michael‐type addition at the meta position is reported. Experimental and theoretical results show that the reaction proceeds via a highly specific interaction between the precursor and the Pt surface that induces the reduction of the aminophenol molecule, opening a door to the rational synthesis of new molecular structures.